Ideologies, utopias and political culture - elements for understanding ideological dispute in Brazil in Coronavirus times - Silva Mazucato, Thiago Pereira da; Burnatelli de Antonio, Gabriel Henrique [UNESP] (Univ Federal Espirito Santo, 2020)
From the concepts of ideology and utopia in the perspective of Karl Mannheim's Sociology of Knowledge, through its crystallization in long-term ideational complexes, such as Brazilian political culture, this article seeks to analyze the way the ideological dispute occurs in the contemporary Brazilian public debate in a scenario of sense crisis resulting from the coronavirus epidemic.
Keywords: Ideologies; utopias; political culture; coronavirus